Use of fibrin sealant in a horse with an intratracheal dorsal laceration. (25th October 2018) - Coco, L.; Dahmen, K.; Bach, N.; Fischer, H.; Albanese, V.; Dylewski, L.; Muñoz, E.
Summary: Dorsal intratracheal laceration was diagnosed in a horse with severe subcutaneous emphysema. Due to the size of the defect and the severity of the symptoms, different methods were attempted to close the laceration. The use of a fibrin sealant is described together with a discussion about other potential treatments and options for this rare condition in the horse.